2021
DOI: 10.18196/jai.v22i2.10773
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Role of Productivity in the Effect of Islamic Corporate Governance on Islamic Corporate Social Responsibility Disclosure

Abstract: Research aims: This study aims to examine the indirect effect of Islamic Corporate Governance on Islamic Corporate Social Responsibility Disclosure.Design/Methodology/Approach:This study uses secondary data sources from annual reports, corporate governance reports, and financial reports of Islamic banking in Indonesia for the period 2008 to 2019, sharia banks that have not been in existence for 12 years, observations have been made since they were established until 2019. The sampling technique is done by conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…If financial statement information is transparent and Islamic social responsibility disclosure demonstrates high accountability, interested people will continue to be loyal investors (Arifin & Wardani, 2016;Arshad et al, 2012). The declaration of Islamic social responsibility does not affect financial performance (Arshad et al, 2012;Budi, 2021). The study results are also consistent with this finding, despite several studies (Arifin & Wardani, 2016;Cahyaningtyas & Canggih, 2020) demonstrating that Islamic social responsibility positively affects ROA to evaluate financial performance.…”
Section: Figure 2 Path Analysis Modelsupporting
confidence: 81%
See 2 more Smart Citations
“…If financial statement information is transparent and Islamic social responsibility disclosure demonstrates high accountability, interested people will continue to be loyal investors (Arifin & Wardani, 2016;Arshad et al, 2012). The declaration of Islamic social responsibility does not affect financial performance (Arshad et al, 2012;Budi, 2021). The study results are also consistent with this finding, despite several studies (Arifin & Wardani, 2016;Cahyaningtyas & Canggih, 2020) demonstrating that Islamic social responsibility positively affects ROA to evaluate financial performance.…”
Section: Figure 2 Path Analysis Modelsupporting
confidence: 81%
“…According to Arshad et al (2012) and Budi's (2021) study, the declaration of Islamic social responsibility has no effect on financial performance. The study results corroborate this finding.…”
Section: Figure 2 Path Analysis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies that are active by implementing social responsibility programs have been empirically proven capable of improving financial performance (Syamni et al, 2018). This aligns with the Good Management Theory statement that CSR is related to the company's financial performance (Budi, 2021). (Riyadh, Al-Shmam, and Firdaus 2022) and (Hermawan et al 2023) state that CSR has a significant effect on financial performance in Indonesian companies.…”
Section: Introductionmentioning
confidence: 57%
“…Most of the studies (Abdullah & Asutay, 2021;Budi, 2021;Jan, Lai, & Tahir, 2021) showed that the implementation of Islamic corporate governance would only do well. It communicates the message of accountability, justice, consultation, integrity, truthfulness, sincerity, intention and brotherhood.…”
Section: Review Of Literaturementioning
confidence: 99%